Dramatizing the Political: Deleuze and Guattari - MacKenzie, I. author. aut Link
VII, 153 p.
Keywords: This is an in-depth analysis of dramatization as method in the work of Deleuze and Guattari. It provides an account of the value of this method for the study of the political with particular emphasis on the relationship between politics and art.